Method for manufacturing orange phosphor and phosphor

JP2025028619APending Publication Date: 2025-03-03TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023133540
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-03-03

AI Technical Summary

Benefits of technology

【0022】 酸化焼成により、還元雰囲気で生成した酸素欠損を減少させることで、青色光と蛍光の光吸収が小さくなるので、蛍光体の内部量子収率は向上する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025028619000002
    Figure 2025028619000002
  • Figure 2025028619000003
    Figure 2025028619000003
  • Figure 2025028619000004
    Figure 2025028619000004
Patent Text Reader

Abstract

To provide a method for manufacturing an orange phosphor that has excellent thermal conductivity.SOLUTION: A method for manufacturing a single crystal including a principal component comprising Gd3(AlSc)5O12 and Ce as an accessory component includes the steps of: filling raw material powder into a crucible; melting the raw material powder in a melt storing part of the crucible; flowing a melt out through a crucible opening part from the melt storing part; and drawing down the melt flowing out from the crucible opening part together with a seed crystal to make a single crystal of the melt, where ScO1.5 / AlO1.5 of the raw material powder is 0.06-0.14.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a phosphor and to a phosphor. [Background technology]

[0002] Spot lighting designed to emit a so-called incandescent light is used for lighting in stores and on the streets.

[0003] In typical incandescent lighting, blue LED light is used as excitation light to hit an orange phosphor, the wavelength is converted to adjust the fluorescent color to orange, and the blue LED light and orange fluorescent light are mixed to produce incandescent lighting.

[0004] However, blue laser light is more suitable than blue LED light as the excitation light for spot lighting, which focuses light on a specific spot. Blue laser light has a smaller light-emitting area than blue LED light, making it easier to focus the light, and is therefore used for spot lighting.

[0005] Reference 1 lists Gd3Al5O as an orange phosphor. 12 :Ce 3+ It has been reported that Gd3Al5O emits orange fluorescence. 12 As described in Reference 2, when organic compounds of Gd and Al are mixed by the sol-gel method and sintered at 1400 °C, a garnet-structured oxide is obtained. Gd3Al5O 12 Ce was added as an activator to Gd3Al5O 12 :Ce 3+ When this is made, it becomes an orange phosphor.

[0006] Simply mixing Gd2O3 and Al2O3 powders and firing them will result in an oxide with a perovskite structure. Even if Ce is added to an oxide with a perovskite structure, it will not emit fluorescence and the oxide will not become a phosphor. 3+ To obtain a phosphor activated with , it is necessary to prepare an oxide with a garnet structure.

[0007] In the literature, 3, an orange phosphor was developed by introducing trivalent cerium as an activator into calcium aluminum silicon nitride, cCaAlSiN3·(1-c)LiSi2N3:Ce 3+ (0.2≦c≦0.8) is disclosed. Such nitride phosphors are known to be susceptible to thermal quenching, and when blue laser light is incident on this orange phosphor, the orange color tends to be lost and the fluorescent light tends not to be the color of an incandescent bulb. In addition, it is difficult to grow single crystals of this nitride material, making it difficult to produce phosphors with good thermal conductivity. [Prior art documents] [Non-patent literature]

[0008] [Non-Patent Document 1] Takeo HATTORI, Shin NISHIYAMA, Muneyuki FUKUDA and Yasuhiko IWADATE, Journal of the Ceramic Society of Japan 100

[11] 1381-1383 (1992) [Non-Patent Document 2] :Jumpei Ueda, Setsuhisa Tanabe, and Takayuki Nakanishi, J. Appl. Phys. 110, 053102 (2011) [Patent documents]

[0009] [Patent Document 1] International Publication No. 2012 / 014702 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in view of the above circumstances, and provides Gd3(AlSc)5O 12 The present invention aims to provide a method for producing an orange phosphor having high thermal conductivity and containing the above as a main component. [Means for solving the problem]

[0011] In order to achieve the above object, the method for producing a crystal according to the present invention comprises the steps of: 12 and Ce as a sub-component, the method for producing a single crystal comprising the steps of: filling a crucible with raw material powder; melting the raw material powder in a melt reservoir of the crucible; causing the melt to flow out of the melt reservoir through an opening of the crucible; and pulling down the melt that has flowed out of the opening of the crucible together with a seed crystal to form a single crystal. 1.5 / AlO 1.5 is between 0.06 and 0.14.

[0012] In the present invention, when Sc2O3 is added to Gd2O3 and Al2O3, melted, and then cooled and solidified, a garnet-structured oxide is formed in which part of Al is replaced by Sc, and a small amount of Ce is added to this oxide. 3+ By adding ScO, an orange phosphor with a garnet structure is produced. 1.5 / AlO 1.5 The inventors discovered that materials with a refractive index of 0.06 to 0.14 have a garnet structure at temperatures near the melting point, and that when single crystals are grown from these materials by the micro-pulling-down method (μ-PD method), single crystals with a garnet structure are obtained. They also discovered that when this single crystal is powdered into single crystal particles and then sintered, an orange phosphor with excellent light scattering properties and thermal conductivity is obtained, which led to the completion of the present invention.

[0013] This makes it possible to emit orange fluorescence (with a fluorescence peak wavelength of 555 nm or more) that can be used for incandescent laser lighting.

[0014] Preferably, the raw material powder (GdO 1.5 +CeO2) / (AlO 1.5 +ScO 1.5 ) is between 0.613 and 0.626.

[0015] This results in (GdCe)3(AlSc)5O with a high internal quantum yield. 12 Since it is possible to grow a garnet single crystal, the internal quantum yield of the phosphor using this single crystal is improved.

[0016] Preferably, the method includes the steps of preparing a single crystal particle powder by pulverizing and classifying the produced single crystal, molding the single crystal particle powder, and sintering the molded body.

[0017] This forms grain boundaries containing voids, which cause some of the blue light and orange fluorescence to be diffusely reflected at the grain boundaries. This effect suppresses in-plane waveguiding of the orange fluorescence, and the blue light and orange fluorescence are sufficiently mixed, improving the light scattering characteristics and allowing the phosphor to project uniform, incandescent light to the outside.

[0018] Preferably, the method includes a step of reducing and firing the molded body.

[0019] By using a carbon furnace that is suitable for high-temperature heating, the molded body can be fired in a high-temperature reducing atmosphere. High-temperature firing in a reducing atmosphere fuses the single crystal particles together, so the single crystal particles adhere to each other without any intervening phase, improving the thermal conductivity of the phosphor.

[0020] However, firing in a reducing atmosphere tends to cause oxygen vacancies, which in turn cause light absorption and tend to reduce the internal quantum yield.

[0021] Preferably, the method includes a step of performing reduction firing of the molded body and then oxidation firing of the molded body.

[0022] Oxidation firing reduces the oxygen vacancies generated in the reducing atmosphere, thereby reducing the light absorption of blue light and fluorescent light, thereby improving the internal quantum yield of the phosphor. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a chart showing the preparation of a phosphor according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a single crystal manufacturing apparatus using a μ-PD method for manufacturing a single crystal that is a material for a phosphor according to one embodiment of the present invention. [Diagram 3]FIG. 3 is a photograph of the surface of the sintered molded body observed with a laser microscope. [Figure 4] FIG. 4 is a diagram showing a diffraction pattern of a phosphor evaluated by the θ-2θ measurement method of X-ray diffraction. [Diagram 5] FIG. 5 shows the excitation light absorption and fluorescent emission of a phosphor measured using a fluorescence spectrophotometer. [Figure 6] FIG. 6 is a schematic diagram of an apparatus for measuring the light intensity ratio. [Figure 7] FIG. 7 is a schematic cross-sectional view of a light emitting device according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, the present invention will be described based on the embodiments shown in the drawings. The phosphor of the present invention is prepared according to the procedure shown in the chart of FIG.

[0025] First, a method for producing a crystal according to one embodiment of the present invention will be described.

[0026] [Material preparation] The materials used are powders of the oxides Gd2O3, Al2O3, Sc2O3 and CeO2 with a purity of 3N. Alumina beads and specified amounts of each oxide material are weighed and added to a plastic airtight container with a lid. The alumina beads act as a medium for mixing the oxide materials. Pure water is then added, the lid is sealed, and the materials are stirred and mixed using a rotation-revolution mixer. The ratio of alumina beads, total oxide weight, and pure water is 3.5:1:2 by weight. The alumina beads mix the various oxides, resulting in oxide materials of uniform composition.

[0027] The stirred and mixed materials are passed through a plastic filter to separate them into alumina beads and oxide materials containing water. The water is then evaporated in a dryer to dry the oxide materials. When the oxide materials dry, they become small plate-like pieces, which are crushed in a mortar and processed into powder to be used as material for crystal growth. By thoroughly mixing the oxide materials to create raw powder with a uniform shape, the reproducibility of single crystal growth conditions is improved.

[0028] [Single crystal] The μ-PD method is superior to conventional CZ methods in that it is easy to grow single crystals even if the main elements are segregated during crystal growth, and it can distribute the activator uniformly. (GdCe)3(AlSc)5O 12 During crystal growth of garnet oxide, Sc segregates.

[0029] When bulk single crystals are grown from compositions with large segregations, stress within the single crystal caused by the segregation can cause the single crystal to crack during growth, leading to changes in temperature conditions, or the broken crystal can fall off, making crystal growth difficult. Single crystals grown by the μ-PD method are rod- or plate-shaped, and are grown downward from the crucible, so even if the crystal cracks due to Sc segregation, growth will not be interrupted by changes in temperature conditions or crystal fall off.

[0030] Since the internal quantum yield of a phosphor increases with improving crystallinity, using a single crystal as the phosphor material is effective for improving the internal quantum yield. For this reason, the phosphor according to this embodiment is produced from a single crystal grown by the μ-PD method.

[0031] [Single crystal growth equipment] Fig. 2 shows a schematic cross-sectional view of a single crystal manufacturing apparatus using the μ-PD method. The μ-PD method is a melting and solidification method. Specifically, in the μ-PD method, a crucible 24 containing a sample is heated directly or indirectly to obtain a melt of the target substance in the crucible 24, and a seed crystal 34 placed below the crucible 24 is brought into contact with an opening 26 at the bottom end of the crucible 24, where a solid-liquid interface is formed, and the seed crystal 34 is pulled down to grow a single crystal.

[0032] 2, the single crystal manufacturing apparatus for manufacturing the phosphor according to this embodiment includes a crucible 24 with an opening 26 facing downward and a refractory furnace 28 that covers the crucible 24. The refractory furnace 28 is further covered by a quartz tube 30, and an induction heating coil 32 for heating the crucible 24 is installed near the center of the quartz tube in the vertical direction.

[0033] A seed crystal 34 held by a seed crystal holding jig 38 is placed in the opening 26 of the crucible 24. An after-heater 36 is also placed near the opening 26 of the crucible 24 to prevent rapid cooling.

[0034] A rod-shaped single crystal is used as the seed crystal 34. The seed crystal 34 can be produced more efficiently when cut from a bulk crystal, so it is preferable that the seed crystal 34 be a single crystal that does not contain any additives.

[0035] [Single crystal growth method] First, a powder material mixture of Gd2O3, Al2O3, CeO2, and Sc2O3, which are raw materials for single crystals, is placed in a crucible 24 inside a refractory furnace. After placing the crucible 24 and after-heater 36 inside the furnace, the surroundings are covered with refractory material, and then a quartz tube 30 and a gas inlet 20 are placed on the outer periphery. After drawing a vacuum inside the furnace, gas such as H2+N2, N2, or Ar is flowed through the gas inlet 20 to replace the inside of the furnace with an inert gas.

[0036] Inert gas is injected 10 to 100 cm from the gas inlet 20 3 1 / min, the crucible is heated by induction heating coil 32 (high frequency coil for heating) to melt the raw materials and obtain a molten liquid.

[0037] Once the material has been melted and the temperature has stabilized, a seed crystal 34 is gradually brought closer to the bottom of the crucible 24 until it comes into contact with the opening 26 at the bottom of the crucible 24. When the melt leaves the opening 26 at the bottom of the crucible 24, the seed crystal 34 is lowered to start crystal growth. The speed at which the seed crystal 34 is lowered here is called the growth speed.

[0038] The growth rate and temperature are controlled by manually adjusting the high frequency output while observing the state of the solid-liquid interface with a CCD camera or a thermo camera. The temperature is controlled so that the solid-liquid interface spreads over the entire opening 26 at the bottom of the crucible.

[0039] The temperature gradient can be selected in the range of 10 to 100° C. / mm by moving the induction heating coil 32. The single crystal growth speed can also be selected in the range of 0.01 to 0.20 mm / min.

[0040] The seed crystal 34 is lowered until the melt in the crucible 24 stops flowing out, and the single crystal is cooled after the seed crystal 34 is separated from the crucible 24. The cooling rate of the single crystal varies depending on the growth rate and can be selected, for example, within the range of 70 to 300° C. / hour.

[0041] [Single crystal powder phosphor] In single crystals grown by the μ-PD method, Sc segregates, so the composition changes from the beginning to the end of the crystal growth, and at the same time, the fluorescence characteristics also change. In order to average out the spectral characteristics of the fluorescence, the single crystal is crushed and processed into powder, which is then thoroughly mixed to produce phosphor 8, which is then molded, fired, and processed. By producing phosphor 8 from powder of single crystal grains, it is possible to produce phosphor 8 with consistent spectral characteristics of fluorescence. At the same time, in-plane waveguiding of the fluorescence is suppressed, and the light scattering characteristics are improved.

[0042] [Powder processing and molding] The single crystals grown by the μ-PD method are crushed into powder using a mortar and pestle, then passed through a stainless steel mesh to produce a powder of single crystal grains. The powder is pressed into a mold to form a pressure shape, and then solidified using CIP (cold isostatic pressing) to produce a compact with solidified single crystal grains. It is preferable to pressurize using CIP to produce a compact, as this creates dense grain boundaries and improves thermal conductivity.

[0043] [Firing] The green body is fired in an argon atmosphere in a carbon furnace. No grain boundary components are added, and single crystal grains are fused together to produce single crystal ceramics. The grain boundaries contain voids, resulting in a shape in which the single crystal grains are partially fused together. As the single crystal grains are fused together, the ceramics have good thermal conductivity. To fuse the single crystal grains together, it is preferable to fire the material in a carbon furnace at a high temperature close to the melting point.

[0044] When the compact is subjected to reduction firing in an atmosphere of an inert gas such as Ar, oxygen vacancies tend to form in the compact. When oxygen vacancies exist, light absorption increases and blue excitation light and fluorescence are absorbed, resulting in a decrease in the internal quantum yield. In order to reduce oxygen vacancies and light absorption, it is preferable to perform oxidation firing of the compact in air after reduction firing.

[0045] [processing] The front and back sides of the fired molded body are polished roughly and precisely to adjust the shape and surface condition. The molded body is then cut into chips using a dicer to produce the phosphor. Polishing and cutting are performed using standard methods used in conventional technology.

[0046] [evaluation] A photograph of the surface of the sintered compact taken with a laser microscope is shown in Figure 3. It has a structure in which single crystal particles 4 have been sintered. Figure 4 shows the results of evaluating the phosphor using the θ-2θ method of X-ray diffraction. Diffraction peaks of the garnet structure and perovskite structure can be seen. The garnet structure is mainly formed, with a small amount of perovskite structure also present. Figure 5 shows the spectral characteristics of excitation light absorption and fluorescence. The spectral characteristics of the phosphor are evaluated by measuring the fluorescence peak wavelength, internal quantum yield, and light absorptivity with a fluorescence spectrophotometer. When the fluorescence peak wavelength is 555 nm or more, the fluorescence becomes orange, and when mixed with blue light LB, warm light LW is obtained. It is preferable that the fluorescence peak wavelength is 555 nm or more.

[0047] The thermal conductivity is measured using a xenon flash method thermal diffusivity measuring device (TD-1, manufactured by ULVAC, Inc.) The thermal conductivity is evaluated based on the shape of the molded body before polishing and cutting.

[0048] The light scattering characteristics were evaluated in terms of the light intensity ratio using the measurement system shown in Figure 6. Blue laser light LB (wavelength 450 nm) was incident from directly above on the center of phosphor 4, and the amount of light LF projected directly upward from phosphor 4 was measured. The ratio of the amount of light LF projected from the periphery of phosphor 8 to the amount of light LF projected from the center of phosphor 4 was calculated as the light intensity ratio.

[0049] If the fluorescence does not propagate in-plane laterally to the light incident surface and light LF does not leak from the outer periphery of the phosphor, the light intensity ratio will be 0. If the fluorescence propagates in-plane, the blue light and fluorescence will separate, resulting in projected light with a mottled color tone. If the light is diffusely reflected at grain boundaries containing voids and in-plane waveguiding of the fluorescence does not occur, the blue light and fluorescence will mix sufficiently within the single crystal grains and light of a single color will be projected. Since the blue light and orange fluorescence will mix sufficiently and become warm light LW, which is projected to the outside, it is preferable for the light intensity ratio to be a small value.

[0050] [Phosphor] As shown in FIG. 7, when blue laser light LB is incident on the phosphor, a part of the blue laser light LB is absorbed by the phosphor 4 and undergoes wavelength conversion, resulting in the emission of fluorescence. The shape of the phosphor 8 according to this embodiment is not particularly limited, and may be, for example, a disk, a flat plate, or a rectangular column, and has a pair of opposing surfaces that function as an incident surface 82 or a reflecting surface 84. EXAMPLES

[0051] The present invention will be described below based on more detailed examples, but the present invention is not limited to these examples.

[0052] [Example 1] Using the single crystal manufacturing apparatus shown in Figure 2, (GdCe)3(AlSc)5O was grown by the following method. 12 A single crystal of was produced.

[0053] The starting materials are Gd2O3, Al2O3, Sc2O3 and CeO2. All the materials are manufactured by High Purity Chemical Laboratory and are 3N purity reagents. GdO 1.537.63mol%, CeO20.38mol%, AlO 1.5 58.28mol%, ScO 1.5 GdO 1.5 6.746g, CeO20.064g, AlO 1.5 2.940g, ScO 1.5 0.254 g was weighed out and placed in a 100 ml plastic container, to which alumina beads and pure water were added, and the container was sealed with a lid.

[0054] The material composition of ScO 1.5 / AlO 1.5 is 0.06, (GdO 1.5 +CeO2) / (AlO 1.5 +ScO 1.5 ) was 0.613.

[0055] The oxide material, beads, and pure water in a plastic container were mixed using a stirring mixer. The mixed oxide material and beads were poured into a filter to separate the beads and oxide material. The filter had a mesh size that did not allow the beads to pass through. The oxide material and pure water separated by the filter were collected in a tray, and the oxide material was dried.

[0056] 2.0 g of the oxide material was weighed out and placed in a Mo crucible 24 having an inner diameter of 16 mm.

[0057] Next, the crucible 24 containing these raw materials was placed in the furnace of a single crystal growth apparatus, and the atmosphere in the furnace was replaced with Ar gas. While maintaining the pressure in the furnace at normal pressure, Ar gas was introduced from the gas inlet 20 to start the single crystal growth operation.

[0058] Thereafter, heating of the crucible 24 was started, and the crucible 24 was heated for one hour until it reached a temperature at which the melt leaked out from the opening 26 .

[0059] A rod-shaped YAG single crystal was used as the seed crystal 34. The tip of the seed crystal 34 was brought into contact with the opening 26 at the bottom end of the crucible, and the seed crystal 34 was pulled down to start crystal growth.

[0060] After about 10 hours of growth, the oxide in the crucible 24 became a single crystal.

[0061] After the growth was completed, the output of the high frequency was reduced and the temperature of the crucible 24 was lowered to room temperature. After the single crystal had cooled to room temperature, it was taken out of the furnace.

[0062] A plate-shaped (GdCe)3(AlSc)5O with a cross-sectional area of ​​2×10 mm and a length of approximately 30 mm 12 Single crystals were grown.

[0063] (GdCe)3(AlSc)5O 12 The single crystal was placed in a mortar and crushed with a pestle. The crushed material was classified using a stainless steel mesh with an opening of 0.33 mm. The crushed material that did not pass through the mesh was crushed again with a mortar and pestle and classified to produce a powder of single crystal particles.

[0064] (GdCe)3(AlSc)5O 12 0.5 g of the single crystal grain powder was weighed out and placed in a die with a diameter of 10 mm. The die was hydraulically pressed to create a disk-shaped compact. After die pressing, the compact was further solidified using the CIP method (Cold Isostatic Pressing) to create a compact with a diameter of 10 mm and a thickness of approximately 1 mm.

[0065] The disk-shaped compact was fired in a reducing atmosphere, and then oxidized in air. The reducing firing was performed in a carbon furnace under the conditions of an Ar atmosphere, firing temperature of 1650°C, and firing time of 12 hours. The oxidized firing was performed in an electric furnace under the conditions of an air atmosphere, firing temperature of 1500°C, and firing time of 12 hours. The compact was fired in an alumina sagger.

[0066] The obtained fired body was processed by rough polishing and precision polishing on the front and back surfaces of the main surface so that the thickness was 0.5 mm. It was then cut into 5.0 mm squares with a dicer to produce phosphors with a shape of 5.0 x 5.0 x 0.5 mm.

[0067] The crystal structure of phosphor 8 was examined by the θ-2θ measurement method of X-ray diffraction (XRD). The measurement results are shown in Figure 4. The diffraction peaks of the garnet structure were the main peaks, but small peaks of the perovskite structure were also observed. A single crystal was grown with perovskite mixed in as a different phase.

[0068] The fluorescence wavelength of phosphor 8 was measured using a fluorescence spectrophotometer. The fluorescence peak wavelength was 559.0 nm. At the same time, the internal quantum yield was also measured, and the fluorescence wavelength of phosphor 8 was 559.0 nm. 3+ Phosphor (chemical formula Y 2.985 Ce 0.015 AlO 12 The internal quantum yield of (GdCe)3(AlSc)5O 12 The phosphor is YAG:Ce 3+ The internal quantum yield for the phosphor was 30.1%.

[0069] The thermal conductivity of phosphor 8 was measured using a laser flash thermal property evaluation device. The thermoelectric conductivity was measured on a fired molded body with a diameter of 10 mm and a thickness of approximately 1 mm. The thermal conductivity was 4.81 W / m·k.

[0070] Blue laser light LB was incident on phosphor 8 from directly above, and the intensity of light LF projected from phosphor 8 was measured by sensor 74 directly above. Since the amount of projected light LF could not be observed from the outer periphery of phosphor 8, it was determined that there was no in-plane waveguiding of fluorescence.

[0071] [Example 2] Phosphor 8 was produced and evaluated in the same manner as in Example 1, except that the material composition of the oxide was changed.

[0072] The raw materials used were all the same as those used in Example 1. GdO 1.5 37.63mol%, CeO20.38mol%, AlO 1.5 54.56mol%, ScO 1.5 GdO 1.5 6.702g, CeO20.063g, AlO 1.5 2.734g, ScO 1.50.504 g was weighed out and placed in a 100 ml plastic container. The subsequent steps of producing phosphor 8, such as single crystal growth, powdering, molding and firing, polishing and cutting, were the same as those in Example 1.

[0073] The material composition of ScO 1.5 / AlO 1.5 is 0.14, (GdO 1.5 +CeO2) / (AlO 1.5 +ScO 1.5 ) was 0.613.

[0074] The crystal phase of phosphor 8 was examined by the θ-2θ measurement method of X-ray diffraction (XRD). The diffraction peaks of the garnet structure were the main peaks, but a small peak of the perovskite structure was observed. A single crystal was grown with perovskite mixed in as a different phase.

[0075] The fluorescence wavelength of phosphor 8 was measured using a fluorescence spectrophotometer. The fluorescence peak wavelength was 556.7 nm. At the same time, the internal quantum yield was also measured, and the fluorescence wavelength of phosphor 8 was 556.7 nm. 3+ Phosphor (chemical formula Y 2.985 Ce 0.015 AlO 12 The internal quantum yield of (GdCe)3(AlSc)5O 12 The phosphor is YAG:Ce 3+ For phosphor 8, the internal quantum yield was about 26.1%.

[0076] The thermal conductivity of phosphor 8 was measured using a laser flash thermal property evaluation device. The thermoelectric conductivity was measured on a fired molded body with a diameter of 10 mm and a thickness of approximately 1 mm. The thermal conductivity was 4.25 W / m·k.

[0077] Blue laser light LB was incident on phosphor 8 from directly above, and the intensity of light LF projected from phosphor 8 was measured by sensor 74 directly above. Since the amount of projected light LF could not be observed from the outer periphery of phosphor 8, it was determined that there was no in-plane waveguiding of fluorescence.

[0078] [Example 3] Phosphor 8 was produced and evaluated in the same manner as in Example 1, except that the material composition of the oxide was changed.

[0079] The raw materials used were all the same as those used in Example 1. GdO 1.5 38.13mol%, CeO20.38mol%, AlO 1.5 57.81mol%, ScO 1.5 GdO 1.5 6.792g, CeO20.063g, AlO 1.5 2.897g, ScO 1.5 0.250 g was weighed out and placed in a 100 ml plastic container. The subsequent steps of producing phosphor 8, such as single crystal growth, powderization, molding and firing, polishing and cutting, were the same as those in Example 1.

[0080] The material composition of ScO 1.5 / AlO 1.5 is 0.06, (GdO 1.5 +CeO2) / (AlO 1.5 +ScO 1.5 ) was 0.626.

[0081] The crystal phase of the phosphor was investigated by the θ-2θ measurement method of X-ray diffraction (XRD). The diffraction peaks of the garnet structure were the main peaks, but a small peak of the perovskite structure was observed. Single crystals containing perovskite as a heterophase were grown.

[0082] The fluorescence wavelength of phosphor 8 was measured using a fluorescence spectrophotometer. The fluorescence peak wavelength was 556.4 nm. At the same time, the internal quantum yield was also measured, and the fluorescence wavelength of phosphor 8 was 556.4 nm. 3+ Phosphor (chemical formula Y 2.985 Ce 0.015 AlO 12 The internal quantum yield of (GdCe)3(AlSc)5O 12 The phosphor is YAG:Ce 3+ The internal quantum yield for the phosphor was 30.5%.

[0083] The thermal conductivity of phosphor 8 was measured using a laser flash thermal property evaluation device. The thermoelectric conductivity was measured on a fired molded body with a diameter of 10 mm and a thickness of approximately 1 mm. The thermal conductivity was 4.99 W / m·k.

[0084] Blue laser light LB was incident on phosphor 8 from directly above, and the intensity of light LF projected from phosphor 8 was measured by sensor 74 directly above. Since the amount of projected light LF could not be observed from the outer periphery of phosphor 8, it was determined that there was no in-plane waveguiding of fluorescence.

[0085] [Example 4] Phosphor 8 was produced and evaluated in the same manner as in Example 1, except that the material composition of the oxide was changed.

[0086] The raw materials used were all the same as those used in Example 1. GdO 1.5 38.13mol%, CeO20.38mol%, AlO 1.5 54.12mol%, ScO 1.5 GdO 1.5 6.748g, CeO20.063g, AlO 1.5 2.695g, ScO 1.5 0.497 g was weighed out and placed in a 100 ml plastic container. The subsequent steps of producing phosphor 8, such as single crystal growth, powdering, molding and firing, polishing and cutting, were the same as those in Example 1.

[0087] The material composition of ScO 1.5 / AlO 1.5 is 0.14, (GdO 1.5 +CeO2) / (AlO 1.5 +ScO 1.5 ) was 0.626.

[0088] The crystal phase of phosphor 8 was examined by the θ-2θ measurement method of X-ray diffraction (XRD). The diffraction peaks of the garnet structure were the main peaks, but a small peak of the perovskite structure was observed. A single crystal was grown with perovskite mixed in as a different phase.

[0089] The fluorescence wavelength of phosphor 8 was measured using a fluorescence spectrophotometer. The fluorescence peak wavelength was 557.2 nm. At the same time, the internal quantum yield was also measured, and the fluorescence wavelength of phosphor 8 was 557.2 nm. 3+ Phosphor (chemical formula Y 2.985 Ce 0.015 AlO 12 The internal quantum yield of (GdCe)3(AlSc)5O 12 The phosphor is YAG:Ce 3+ The internal quantum yield for the phosphor was 27.0%.

[0090] The thermal conductivity of phosphor 8 was measured using a laser flash thermal property evaluation device. The thermoelectric conductivity was measured on a fired molded body with a diameter of 10 mm and a thickness of approximately 1 mm. The thermal conductivity was 4.12 W / m·k.

[0091] Blue laser light LB was incident on phosphor 8 from directly above, and the intensity of light LF projected from phosphor 8 was measured by sensor 74 directly above. Since the amount of projected light LF could not be observed from the outer periphery of phosphor 8, it was determined that there was no in-plane waveguiding of fluorescence.

[0092] The phosphors evaluated in the examples were ceramics made by fusing single crystal particles, so there was no in-plane waveguiding of fluorescent light in any of them, and they exhibited the characteristic of high thermal conductivity.

[0093] [Comparative Example 1] Phosphor 8 was produced and evaluated in the same manner as in Example 1, except that the material composition of the oxide was changed.

[0094] The raw materials used were all the same as those used in Example 1. GdO 1.5 37.63mol%, CeO20.38mol%, AlO 1.5 60.14mol%, ScO 1.5 GdO 1.5 6.769g, CeO20.064g, AlO 1.5 3.044g, ScO 1.50.127 g was weighed out and placed in a 100 ml plastic container. The subsequent steps of producing phosphor 8, such as single crystal growth, powdering, molding and firing, polishing and cutting, were the same as those in Example 1.

[0095] The material composition of ScO 1.5 / AlO 1.5 is 0.03, (GdO 1.5 +CeO2) / (AlO 1.5 +ScO 1.5 ) was 0.613.

[0096] The crystal phase of phosphor 8 was examined by the θ-2θ measurement method of X-ray diffraction (XRD). Diffraction peaks of perovskite structure and garnet structure were mixed. Crystals were grown in which perovskite was mixed as a different phase.

[0097] The fluorescence wavelength of phosphor 8 was measured using a fluorescence spectrophotometer. The fluorescence peak wavelength was 554.1 nm. 1.5 As a result of reducing the wavelength, the peak wavelength shifted to the shorter wavelength side.

[0098] At the same time, the internal quantum yield was also measured. 3+ Phosphor (chemical formula Y 2.985 Ce 0.015 AlO 12 The internal quantum yield of (GdCe)3(AlSc)5O 12 The phosphor is YAG:Ce 3+ The internal quantum yield for the phosphor was 29.5%.

[0099] The thermal conductivity of phosphor 8 was measured using a laser flash thermal property evaluation device. The thermoelectric conductivity was measured on a fired molded body with a diameter of 10 mm and a thickness of approximately 1 mm. The thermal conductivity was 4.09 W / m·k.

[0100] Blue laser light LB was incident on phosphor 8 from directly above, and the intensity of light LF projected from phosphor 8 was measured by sensor 74 directly above. Since the amount of projected light LF could not be observed from the outer periphery of phosphor 8, it was determined that there was no in-plane waveguiding of fluorescence.

[0101] [Comparative Example 2] Phosphor 8 was produced and evaluated in the same manner as in Example 1, except that the material composition of the oxide was changed.

[0102] The raw materials used were all the same as those used in Example 1. GdO 1.5 37.63mol%, CeO20.38mol%, AlO 1.5 50.84mol%, ScO 1.5 GdO 1.5 6.658g, CeO20.063g, AlO 1.5 2.531g, ScO 1.5 0.751 g was weighed out and placed in a 100 ml plastic container. The subsequent steps of producing phosphor 8, such as single crystal growth, powdering, molding and firing, polishing and cutting, were the same as those in Example 1.

[0103] The material composition of ScO 1.5 / AlO 1.5 is 0.22, (GdO 1.5 +CeO2) / (AlO 1.5 +ScO 1.5 ) was 0.613.

[0104] The crystalline phase of phosphor 8 was examined by the θ-2θ measurement method of X-ray diffraction (XRD). Only the diffraction peaks of the garnet structure were measured.

[0105] The fluorescence wavelength of the phosphor was measured using a fluorescence spectrophotometer. The fluorescence peak wavelength was 555.8 nm. The fluorescence peak wavelength shifted to the short wavelength side, and fluorescence 8 was close to yellow in color. At the same time, the internal quantum yield was also measured, and the fluorescence of YAG:Ce 3+ Phosphor (chemical formula Y 2.985 Ce 0.015 AlO 12 The internal quantum yield of (GdCe)3(AlSc)5O 12 The phosphor is YAG:Ce 3+ The internal quantum yield for the phosphor was low at 19.3%.

[0106] The thermal conductivity of phosphor 8 was measured using a laser flash thermal property evaluation device. The thermoelectric conductivity was measured in the form of a molded body with a diameter of 10 mm and a thickness of approximately 1 mm. The thermal conductivity was 5.01 W / m·k.

[0107] Blue laser light LB was incident on phosphor 8 from directly above, and the intensity of light LW projected from phosphor 8 was measured by sensor 74 directly above. Since the amount of projected light LF could not be observed from the outer periphery of phosphor 8, it was determined that there was no in-plane waveguiding of fluorescence.

[0108] The material compositions, fluorescence peak wavelengths, thermal conductivities, and internal quantum yields of the examples and comparative examples are summarized in Table 1. With material compositions in the range enclosed by Examples 1 to 4, phosphors with relatively good internal quantum yields and orange fluorescence suitable for laser illumination can be produced. [Table 1] [Explanation of symbols]

[0109] 2… Crystal manufacturing equipment 20…Gas inlet 24… Crucible 26… Crucible opening 28… Refractory furnace 30…Quartz tube 32... Induction heating coil 34… Seed crystal 36... After heater 38… Seed crystal holding jig 4 … Crystalline particles 70... Blue light emitting element, blue laser light source 72…Dichroic mirror 74…CCD camera LB: Excitation light, blue light, blue laser light LF: Fluorescence LW…warm light 8. Phosphor 82…Incidence plane 84… Reflective surface

Claims

1. G.D. 3 (AlSc) 5 O 12 and Ce as a sub-component, the method for producing a single crystal includes the steps of: filling a crucible with raw material powder; melting the raw material powder in a melt reservoir of the crucible; causing the melt to flow out of the melt reservoir through an opening of the crucible; and pulling down the melt that has flowed out of the opening of the crucible together with a seed crystal to form a single crystal. 1.5 / AlO 1.5 A method for producing an orange phosphor having a luminance of 0.06 to 0.

14.

2. In the raw material powder (GdO 1.5 + CeO 2 ) / (AlO 1.5 +ScO 1.5 2. The method for producing an orange phosphor according to claim 1, wherein the value of n is 0.613 to 0.

626.

3. 3. A method for producing an orange phosphor, comprising the steps of: preparing a single crystal particle powder by pulverizing and classifying the single crystal produced by the method of claim 1 or 2; molding the single crystal particle powder to prepare a green body; and sintering the green body to produce a phosphor.

4. The method for producing an orange phosphor according to claim 3 , further comprising the step of subjecting the molded body to reduction firing and then oxidation firing.

5. (GdCe) 3+x A 5-y S.C. y O 12 A phosphor having a garnet-type crystal structure represented by the formula: GdO 1.5 + CeO 1.5 is 38.0 mol% or more and 38.6 mol% or less, AlO 1.5 is 54.1 mol% or more and 58.3 mol% or less, ScO 1.5 has a composition of 3.6 mol % or more and 7.5 mol % or less, (GdO 1.5 + CeO 1.5 ) / (AlO 1.5 +ScO 1.5 ) is 0.61 or more and 0.63 or less, and ScO 1.5 / AlO 1.5 A phosphor having a value of 0.06 or more and 0.14 or less.

6. 6. The phosphor according to claim 5, wherein said phosphor is a sintered body obtained by molding and sintering single crystal particles.

Citation Information

Patent Citations

  • Light-emitting device

    WO2012014702A1